Blocking CCL8-CCR8–Mediated Early Allograft Inflammation Improves Kidney Transplant Function. Issue 10 (October 2022) - Dangi, Anil; Husain, Irma; Jordan, Collin Z.; Yu, Shuangjin; Natesh, Naveen; Shen, Xiling; Kwun, Jean; Luo, Xunrong
Significance Statement: In a mouse allograft model, the CCL8-CCR8 axis mediated early kidney inflammation through donor kidney resident macrophages. The revealed therapeutic targets could expand the transplantable donor kidney pool and promote kidney allograft longevity. Visual Abstract: Abstract : Background: In kidney transplantation, early allograft inflammation impairs long-term allograft function. However, precise mediators of early kidney allograft inflammation are unclear, making it challenging to design therapeutic interventions. Methods: We used an allogeneic murine kidney transplant model in which CD45.2 BALB/c kidneys were transplanted to CD45.1 C57BL/6 recipients. Results: Donor kidney resident macrophages within the allograft expanded rapidly in the first 3 days. During this period, they were also induced to express a high level of Ccl8, which, in turn, promoted recipient monocyte graft infiltration, their differentiation to resident macrophages, and subsequent expression of Ccl8 . Enhanced graft infiltration of recipient CCR8 + T cells followed, including CD4, CD8, and γδ T cells. Consequently, blocking CCL8-CCR8 or depleting donor kidney resident macrophages significantly inhibits early allograft immune cell infiltration and promotes superior short-term allograft function. Conclusions: Targeting the CCL8-CCR8 axis is a promising measure to reduce early kidney allograft inflammation.